Comparative Study of Electricity Generation Fueled by Gasoline, Liquefied Petroleum Gas and Biogas from Municipal Solid Waste - Seno Darmawan Panjaitan; Yandri Yandri; Sukandar Sukandar; Berlian Sitorus (Institute of Advanced Engineering and Science, 2013)
This paper presents a comparative study in terms of power quality and fuel consumption in electricity generation using three kinds of fuel: gasoline, liquefied petroleum gas (LPG) and biogas from anaerobic digestion of municipal solid waste. The electrical parameters measured and compared are voltage, current, frequency, active power, apparent power, reactive power, power factor, displacement power factor, current harmonics, voltage harmonics, transient, sags and swell. From the experiment, resistive loads (100 W bulb and 2 x 100 W bulbs) and resistive-inductive load (125 W water pump) were used as loads of generator set. It can be seen that in general, the power quality among those three fuels shows almost the similar performance. The problem on using combustible gases, either LPG or biogas, significantly appears at the frequency with greatly difference to the standard (i.e. 50 Hz).DOI:http://dx.doi.org/10.11591/ijece.v3i6.3942